Aplikasi Android untuk Validasi Berkas Tes Covid-19 - Viving Frendiana; Fahmi Febriyansyah (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2022)
During the pandemic, everyone will carry out activities, everyone must have a Covid-free letter, especially when traveling. The impact of the pandemic everyone must be able to prevent the spread of the virus by minimizing direct contact. The use of mobile applications can be used to simplify and streamline every activity carried out during the pandemic. Therefore, currently we need a system that can be used as access to activities based on health certificates. An application system in the form of an android called Sudah Sehat can be a system that can be used. Based on testing the functional suitability and portability aspects, the Sudah Sehat application obtained a test score of 100% according to the Black Box Testing and Firebase Test Lab tests. From the aspect of performance efficiency, CPU usage when running applications is below the percentage of 15% which indicates that it is still in the safe limit. All applications also meet the eligibility standards based on ISO 25010.